1989
DOI: 10.1128/mcb.9.1.259
|View full text |Cite
|
Sign up to set email alerts
|

A block in mammalian splicing occurring after formation of large complexes containing U1, U2, U4, U5, and U6 small nuclear ribonucleoproteins.

Abstract: The assembly of mammalian pre-mRNAs into large 50S to 60S complexes, or spliceosomes, containing small nuclear ribonucleoproteins (snRNPs) leads to the production of splicing intermediates, 5' exon and lariat-3' exon, and the subsequent production of spliced products. Influenza virus NS1 mRNA, which encodes a virus-specific protein, is spliced in infected cells to form another viral mRNA (the NS2 mRNA), such that the ratio of unspliced to spliced mRNA is 10 to 1. NS1 mRNA was not detectably spliced in vitro wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…It was shown previously that despite the almost total absence of splicing intermediates in the in vitro reaction, intact NS1 mRNA efficiently formed ATP-dependent 55S complexes containing the Ul, U2, U4, U5, and U6 snRNPs (1). If these 55S complexes represented authentic spliceosome species that were, however, blocked in the subsequent catalysis of splicing, then intact NS1 mRNA and spliceable NS1 mRNA lacking the inhibitory exon and intron sequences should form 55S complexes with similar, if not identical, efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown previously that despite the almost total absence of splicing intermediates in the in vitro reaction, intact NS1 mRNA efficiently formed ATP-dependent 55S complexes containing the Ul, U2, U4, U5, and U6 snRNPs (1). If these 55S complexes represented authentic spliceosome species that were, however, blocked in the subsequent catalysis of splicing, then intact NS1 mRNA and spliceable NS1 mRNA lacking the inhibitory exon and intron sequences should form 55S complexes with similar, if not identical, efficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…This type of splicing regulation also occurs with retroviruses. In in vitro splicing reactions, NS1 mRNA forms 55S complexes containing the Ul, U2, U4, U5, and U6 snRNPs, but little or no catalysis of the first step in splicing occurs (1,28). The cause of this block in catalysis was not determined, but the available data argued against the involvement of the 5' and 3' splice sites and branchpoint of NS1 mRNA in this block.…”
mentioning
confidence: 90%
“…Although a similar effect was not observed with a large truncation of the env pre-mRNA intron including these elements (Katz and Skalka 1990), the negative elements may function only in a certain sequence context. Negative elements may also play a role in incomplete splicing of influenza virus NSl mRNA (Plotch and Krug 1986;Agris et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA products were analyzed by gel electrophoresis. The identities of the premRNA and splicing products, which have been established previously (Fumeaux et al 1985;Perkins et al 1986;Agris et al 1989;Krainer et al 19901, are indicated schematically: [] and 9 correspond to the 5' and 3' exons, respectively; thin lines correspond to the intron, which is converted to a lariat form during splicing.…”
Section: The Ns1 Protein Inhibits Pre-mrna Splicing In Vitromentioning
confidence: 99%
“…A [3-globin minigene in pGEM1 linearized with EcoRI and the adenovirus pKT1 minigene in sp65 linearized with ScaI were transcribed with SP6 RNA polymerase, as described previously (Agris et al 1989). The in vitro transcripts contained -3x 107 cpm (derived from [a-g2P]UTP/~g and contained mZGpppG 5' ends.…”
Section: In Vitro Splicing Assays and Native Gel Electrophoresismentioning
confidence: 99%